Characterization and prognostic relevance of circulating microvesicles in chronic lymphocytic leukemia. Issue 6 (3rd June 2017) - De Luca, Luciana; D'Arena, Giovanni; Simeon, Vittorio; Trino, Stefania; Laurenzana, Ilaria; Caivano, Antonella; La Rocca, Francesco; Villani, Oreste; Mansueto, Giovanna; Deaglio, Silvia; Innocenti, Idanna; Laurenti, Luca; et al.
Abstract: Microvescicles (MV) are shedding particles released by normal and neoplastic cells, whose levels in biological fluids highlight their potential role as disease biomarkers and therapeutic targets. By analyzing 131 newly diagnosed chronic lymphocytic leukemia (CLL), we found that the absolute number of serum CLL MV was significantly higher than in controls, in particular in advanced stages of disease. In addition, CD19 + and CD37+, B-cell derived MV, significantly correlated with high tumor burden. Absolute MV number cutoff selected by ROC analysis distinguished Rai stage 0 patients with shorter time to treatment (TTT) from those with more stable disease. Likewise, in the entire cohort, two groups of patients with different overall survival (OS) and different TTT were identified. At multivariate analysis, serum MV independently predicted for OS (along with Rai stage) and TTT (along with Rai stage, lymphocytes and CD38). In conclusion, circulating MV represent a new potential prognostic biomarker in CLL.